Chondrogenic differentiation of ATDC5 and hMSCs could be induced by a novel scaffold‐tricalcium phosphate‐collagen‐hyaluronan without any exogenous growth factors in vitro. Issue 8 (24th September 2013) - Meng, Fangang; He, Aishan; Zhang, Zhiqi; Zhang, Ziji; Lin, Zihong; Yang, Zibo; Long, Yi; Wu, Gang; Kang, Yan; Liao, Weiming
Abstract Application of chondrogenic growth factors is a routine strategy to induce chondrogenesis of hMSCs, but they have economic and safety problems in the long term. It is expected that scaffold material itself could play an important role in chondrogenesis of hMSCs. In this study we tested whether a novel tricalcium phosphate‐collagen‐hyaluronan scaffold (TCP‐COL‐HA) had inherent chondro‐inductive capacity for chondrogenesis of both ATDC5 and hMSCs without any exogenous growth factors in vitro. hMSCs and ATDC5 were seeded onto TCP‐COL‐HA scaffolds and cultured in basal medium for 3 weeks to investigate whether the TCP‐COL‐HA scaffold itself had differentiation‐inductive capacity in basal culture. With hMSCs‐seeded scaffold in chondrogenic medium (including TGF‐β1) as positive control, we then compared the chondrogenic induction of TCP‐COL‐HA in basal culture and in chondrogenic culture. The chondrogenic differentiation was evaluated by sulfated glycosaminoglycans (GAGs) quantification, type II collagen immunohistochemistry, and RT‐PCR. Mechanical strength was evaluated by compression test and the cell death rate of hMSCs was assessed with TUNEL assay. The results showed TCP‐COL‐HA scaffold itself could efficiently induce chondrogenic differentiation of both ATDC5 and hMSCs after 3 weeks in basal culture. The accumulation of GAGs and the expression of chondrocyte marker genes were all significantly increased. In addition, hMSCs‐seeded scaffold showed a significantly higher mechanical strength after 3 weeks in basal culture. The chondrogenic induction of TCP‐COL‐HA scaffolds in basal medium were almost similar to that in chondrogenic medium on hMSCs. The chondrogenesis‐inducing capacity of TCP‐COL‐HA scaffold might help to improve cartilage tissue engineering with economic and safe benefits. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 2725–2735, 2014.